Discourses on Business Education at the College Level : On the Boundaries of Content and Praxis - Brock, Sabra E.; McAliney, Peter J. (Touro University Press books., 2019)
Drawing from doctoral level research on how best to teach business education to college students, Discourses on Business Education at the College Level illustrates new and proven ideas for engaging students. Sixteen authors from New York University's Steinhardt School of Culture, Education, and Human Development describe their experiences in upgrading and expanding the quality of the business education experience. Business school instructors can use this edited collection to draw inspiration and learn specific techniques to bring their courses to the cutting edge of curriculum. Topics range from teaching accounting, financial literacy, marketing, and teamwork to gamification, improving international student and intern experience, not-for credit education, and virtual workplace learning.